A Retrospective Pilot Study Using Cone-Beam Computed Tomography to Assess the Morphology and Anatomy of the Nasopalatine Canal - M L Avinash Tejasvi; CH Katyayani Devi; M Julia Mary Rachel; Cholleti Sowmya; Mounika Reddy Mekala; V Keerthi Reddy (Wolters Kluwer Medknow Publications, 2023)
Background: The neurovascular bundle-rich nasopalatine canal (NPC), a significant anatomical marker in the premaxillary area, must be conserved during surgical treatments. The morphology and anatomy of the NPC are difficult to evaluate with conventional radiographic imaging. However, cone-beam computed tomography (CBCT) offers three-dimensional images of the NPC in axial, coronal, and sagittal sections, which are useful for premaxillary surgical procedures. Objectives: Using CBCT, this study aimed to assess the anatomical and morphological aspects of the NPC and its relationship with gender. Methods: A retrospective analysis was performed on 50 CBCT patients. The morphology of the NPC was categorized, sizes and forms were measured, and gender variances were assessed and statistically analyzed. Results: Males had higher morphometric values for NPC length and anterior nasal spine (ANS)-to-posterior nasal spine (PNS) length. Conclusions: Preoperative evaluation of the NPC by CBCT is essential, particularly for the significant planning of surgical procedures. This study's CBCT findings highlighted the anatomical and morphologic variability of NPC between both genders and found a significant difference between males and females in relation to NPC length and ANS-to-PNS length. More of a common shape, with a single canal, is found in males.